Kemampuan Koneksi Matematis Siswa dengan Probing Prompting Berdasarkan Nilai-nilai Islam Pada Materi Pola Bilangan - Ika Meika; Nenden Suciyati Sartika; Asep Sujana; Ridwan (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2020)
This study aims to determine an increase in the mathematical connection ability of students of class VIII MTs Mathlabul Falah Labuan by using the Probing-prompting learning model based on Islamic values. The method used in this study is quasi-experimental method. Sampling was done by sampling technique saturated with a sample of 40 students from class VIII A as the experiment class and class VIII B as the control class. Based on the results of data analysis, the results show that there are differences in the ability to improve mathematical connections between experimentasl class students and control class students. Keywords: Probing-Prompting, Mathematical Connection